Effects of lumacaftor—ivacaftor therapy on cystic fibrosis transmembrane conductance regulator function in F508del homozygous patients with cystic fibrosis aged 2–11 years - Berges, Julian; Graeber, Simon Y.; Hämmerling, Susanne; Yu, Yin; Krümpelmann, Arne; Stahl, Mirjam; Hirtz, Stephanie; Scheuermann, Heike; Mall, Marcus A.; Sommerburg, Olaf (Frontiers in Pharmacology, 2023)
Rationale: Lumacaftor/ivacaftor was approved for the treatment of patients with cystic fibrosis who are homozygous for F508del aged 2 years and older following positive results from phase three trials. However, the improvement in CFTR function associated with lumacaftor/ivacaftor has only been studied in patients over 12 years of age, while the rescue potential in younger children is unknown. Methods: In a prospective study, we aimed to evaluate the effect of lumacaftor/ivacaftor on the CFTR biomarkers sweat chloride concentration and intestinal current measurement as well as clinical outcome parameters in F508del homozygous CF patients 2–11 years before and 8–16 weeks after treatment initiation. Results: A total of 13 children with CF homozygous for F508del aged 2–11 years were enrolled and 12 patients were analyzed. Lumacaftor/ivacaftor treatment reduced sweat chloride concentration by 26.8 mmol/L (p = 0.0006) and showed a mean improvement in CFTR activity, as assessed by intestinal current measurement in the rectal epithelium, of 30.5% compared to normal (p = 0.0015), exceeding previous findings of 17.7% of normal in CF patients homozygous for F508del aged 12 years and older. Conclusion: Lumacaftor/ivacaftor partially restores F508del CFTR function in children with CF who are homozygous for F508del, aged 2–11 years, to a level of CFTR activity seen in patients with CFTR variants with residual function. These results are consistent with the partial short-term improvement in clinical parameters.